Ambulatory induction phase treatment of cryptococcal meningitis in HIV integrated primary care clinics, Yangon, Myanmar - Warrell, CE; Macrae, C; McLean, ARD; Wilkins, E; Ashley, EA; Smithuis, F; Tun, NN (BioMed Central, 2021)
Background Cryptococcal meningitis (CM) is a common HIV-associated opportunistic-infection worldwide. Existing literature focusses on hospital-based outcomes of induction treatment. This paper reviews outpatient management in integrated primary care clinics in Yangon. Method This retrospective case note review analyses a Myanmar HIV-positive patient cohort managed using ambulatory induction-phase treatment with intravenous amphotericin-B-deoxycholate (0.7–1.0 mg/kg) and oral fluconazole (800 mg orally/day). Results Seventy-six patients were diagnosed between 2010 and 2017. The median age of patients diagnosed was 35 years, 63% were male and 33 (45%) were on concurrent treatment for tuberculosis. The median CD4 count was 60 at the time of diagnosis. Amphotericin-B-deoxycholate infusions precipitated 56 episodes of toxicity, namely hypokalaemia, nephrotoxicity, anaemia, febrile reactions, phlebitis, observed in 44 patients (58%). One-year survival (86%) was higher than existing hospital-based treatment studies. Conclusion Ambulation of patients in this cohort saved 1029 hospital bed days and had better survival outcomes when compared to hospital-based studies in other resource constrained settings.